1987 second best in recent years for grain dust explosions - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Fourteen grain dust explosions were reported in the U.S. in 1987 according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This compares to 21 in 1986 and a 10 year average of 21 explosions.
Keywords: Grain dust; Dust explosions